Cultural Values and Political Socialization: A Comparative Study - Pulami Magar, Rudra Bahadur (DMC Journal, 2025)
Political socialization is defined as the process by which individuals acquire their political knowledge, beliefs, values, and behaviors, which shape their participation in public life and political attitudes. While traditional approaches have focused on education, legal structures, and formal political institutions, this study specifically emphasizes the central role of cultural values ​​in political socialization. Through the analysis of secondary data from Nepal, South Asia, and Western democracies, the study examines how family, religion, language, community practices, and historical experiences influence citizens’ political awareness, democratic values, and participatory behaviors. The findings show that collectivism, hierarchy, and traditional beliefs have a strong influence on political socialization in Nepal and South Asian societies, while individual freedom, liberal values, and participatory cultures dominate in Western societies. In addition, globalization and digital media have created complex interactions between traditional and modern political values, especially among the younger generation. These scenarios present both opportunities for increased democratic participation and challenges such as the conflict between hierarchy and participatory expectations. This shows that understanding political socialization requires incorporating cultural, historical, and global perspectives.